Editorial Numen 2019 1 - Quaglio de Souza, Humberto Araújo; Correia Lages, Sônia Regina; Adogame, Afe; Fanuel Xavier Rodrigues, Felipe; Barreto Junior, Raimundo César (Numen, 2020)
Editorial Numen 2019 1